Easy-to-read German put to the test: do adults with intellectual disability or functional illiteracy benefit from compound segmentation? - Pappert, Sandra; Bock, Bettina M. (Reading and writing, 2020)
Easy-to-read (ETR) German is the subject of public debate. Even though it is heavily promoted by officials, its status is controversial. Moreover, the comprehensibility of ETR German texts awaits systematic testing. The aim of the present study was to test a controversial rule concerning word segmentation. Hypotheses derived from psycholinguistic studies with skilled readers predict an interaction of segmentation and semantic transparency. A sample of individuals, some with intellectual disability and others functionally illiterate, performed a timed lexical decision task on unsegmented and segmented noun compounds that were either semantically transparent or semantically opaque. The results show an advantage of segmentation that was not modulated by semantic transparency. At the same time, a main effect of semantic transparency indicates that the meaning of the compounds was accessed. Two potential loci of the segmentation advantage are discussed: a prelexical one referring to phonological recoding and a lexical one related to access to phonological word forms. The outcome of the experiment approves the practice of segmenting noun compounds in ETR German. The study further attests the feasibility and potential fruitfulness of experimental research with target groups of ETR.
Published online: 15 November 2019
Gesehen am 28.05.2020